Building Public Trust through The Excellency Program; A Study on Tahfidz Branding in Pesantren - Rahmawati, Ima; Anwar, Harles; Wathoni, Kharisul; Maromi, Izzul (JURNAL AL-TANZIM, 2023)
This study aims to understand the tahfidz branding strategy by Islamic boarding schools to build public trust. This study uses a qualitative approach, using interviews, observation and documentation to obtain valid and accurate data. The data analysis was carried out circularly, starting with data collection, data reduction, data presentation and concluding. The results showed that the branding of tahfidz Al-Qur'an at the Pondok Pesantren Nurul Jadid and Pondok Pesantren Modern Sahid in building public trust was carried out through sima'an activities, syi'ar through You Tube media, Musabaqoh Al-Qur'an, delegation to caravans in various activities. This research has implications for the importance of designing a superior product for educational institutions as a medium to increase public trust.